Pengaruh disiplin kerja dan komitmen organisasi terhadap kinerja pegawai dengan gaya kepemimpinan sebagai variabel intervening di PT. Rijan Dinamis Selaras (RDS) Pacet Mojokerto - Ali Imron Mashadi (Sekolah Tinggi Ilmu Ekonomi Syariah Riyadlul Jannah Mojokerto, 2022)
The objectives of this study are: 1) To analyze the effect of work discipline on leadership styles. 2) Analyzing the effect of organizational commitment on leadership style. 3) Analyze work discipline on employee performance. 4) Analyzing the effect of organizational commitment on employee performance. 5) Analyze the influence of leadership style on employee performance. 6) Analyze work discipline on employee performance with leadership style as an intervening variable. 7) Analyzing the effect of organizational commitment on employee performance with leadership style as an intervening variable. The population in this study were all employees at PT. Rijan Dinamis Selaras (RDS) Pacet Mojokerto totaling 33 people. The sampling method in this writing uses census technique. Data analysis used SPSS version 20 to test the validity with factor analysis, reliability test with Cronbach alpha. Classic assumption test and multiple linear regression analysis, to verify and prove the research hypothesis. From the research results it can be concluded as follows: 1) Work discipline has no effect on leadership style 2) Organizational commitment has a significant effect on leadership style 3) Work discipline has no effect on employee performance 4) Organizational commitment has no effect on employee performance 5) Leadership style has a significant effect Employee performance 6) Work discipline has an indirect effect on employee performance through leadership styles 7) Organizational commitment has an indirect effect on employee performance through leadership styles.